Monopolizing violence in a colonial frontier. The Police and the Army in southern Patagonia (Argentina and Chile, 1870-1922) (Quinto Sol, 2016)
This article analyses the State’s monopolization of the violence in the early cycle of southern Patagonia colonization, proposing first, that the local precariousness of Argentinean and Chilean states relied upon the expansive strength of the sheep farming industry for materializing their territorial sovereignty; and, secondly, that the enclosure of the international delimitation in the summer of 1922 resulted from the repression of the workers’ insurgency. Based on a wide research on official and entrepreneurial sources, on Santa Cruz, Magallanes and Tierra del Fuego, as well as on local press, it examines and compares the presence of police and military forces in the extreme South, explaining the similitudes and differences of the strategies of social control.
Keywords: state building; colonialism; monopoly of violence; sovereignty; frontier studies